THE INFLUENCE OF SOCIAL MEDIA ON ISLAMIC LEARNING METHODS IN THE SCOPE OF HIGHER EDUCATION - Muhammad Ilham Firdaus; Miftahul Jannah Lubis; Rahma Sinta (Proceeding International Seminar of Islamic Studies, 2022)
This article is motivated by a situation where people are slowly drifting away from the teachings of Islam due to the modernization process which has influenced on a person's concern for deepening their understanding of religiosity. The creation of effective learning methods in this modern era cannot be separated from the influence of the strategies used in learning and the use of tools such as social media in the learning. Strategies and working methods that support the creation of learning methods will provide effectiveness in the implementation process. The research method used is a case study method, and qualitative data collection. This article provides information about how significant the influence of Islamic learning through social media is in the scope of Higher Education.Keywords : Islamic Learning Method, Higher Education, Social Media